Trifectas for T-N in 5d - Eckhard, J; Schafer-Nameki, S; Wang, Y-N (Springer, 2020)
The trinions TN are a class of 5d N = 1 superconformal field theories (SCFTs) realized as M-theory on ℂ3/ℤN × ℤN . We apply to TN, as well as closely-related SCFTs that are obtained by mass deformations, a multitude of recently developed approaches to studying 5d SCFTs and their IR gauge theory descriptions. Thereby we provide a complete picture of the theories both on the Coulomb branch and Higgs branch, from various geometric points of view — toric and gluing of compact surfaces as well as combined fiber diagrams — to magnetic quivers and Hasse diagrams.